The Passion Fruit in Florida - Mark Bailey; Ali Sarkhosh; Amir Rezazadeh; Joshua Anderson; Alan Chambers; Jonathan H. Crane (EDIS)
Passion fruit is a short-lived evergreen perennial vine that produces an aromatic and tropical-tasting fruit. This new 13-page publication of the UF/IFAS Horticultural Sciences Department provides a description of passion fruit and its various species and cultivars, as well as a guide to culture and management, harvest and storage, its pests and diseases, and food and marketing. Written by Mark Bailey, Ali Sarkhosh, Amir Rezazadeh, Joshua Anderson, Alan Chambers, and Jonathan Crane. https://edis.ifas.ufl.edu/hs1406